MEDIA PERMAINAN MERONCE BERPENGARUH TERHADAP KEMAMPUAN ANAK USIA DINI DALAM MENGENAL BENTUK GEOMETRI - Aisyah (LPPM Universitas PGRI Adi Buana, 2024)
Early Childhood Education (PAUD) is a coaching effort aimed at children from birth to the age of six, through the provision of educational stimuli, as a form of assistance for physical and spiritual growth and development so that children are ready to enter education. Based on the results of field observations made to Tk.A students, children still experience difficulties in recognizing patterns. They still can't sort the 2 predefined patterns. Children tend not to follow the pattern set by the teacher. This is because the pattern concept recognition activity is given using an activity book. This results in children feeling bored and bored when doing tasks in recognizing patterns. In pattern recognition, you must use activities that make it easier for children to recognize patterns. The activities provided are in the form of play activities, because basically the child's world is the world of play. Data analysis technique using t-test. From the results of the analysis of hypothesis testing, it was shown from the results of data analysis that the tcount of 31.25 was greater than the ttable of 1.72913 at the achieved level of 0.05 and 2.53948 and at the reached level of 0.01. This shows that the t table value is smaller than the calculated t value both at a significance level of 0.05 and at a level of 0.05 and at a level of 0.01. Thus the Null Hypothesis is rejected so that the Working Hypothesis is accepted. From the table it can also be seen that the calculated t value is greater than the t table value at both levels achieved, so that it can be said that the Working Hypothesis is significantly proven. Thus it can be concluded that the meronce game media influences the ability of children at the age of 4-5 years to recognize geometric shapes. Keywords : Meronce game media, Early Childhood, Geometric Shapes. Abstrak Pendidikan Anak Usia Dini (PAUD) adalah upaya pembinaan yang ditujukan kepada anak sejak lahir hingga usia enam tahun, melalui pemberian rangsangan pendidikan, sebagai bentuk bantuan tumbuh kembang jasmani dan rohani agar anak siap memasuki jenjang pendidikan. Berdasarkan hasil observasi lapangan yang dilakukan kepada siswa Tk.A pada salah satu sekolah TK , anak masih mengalami kesulitan dalam mengenali pola. Mereka masih tidak dapat mengurutkan 2 pola yang telah ditentukan. Anak-anak cenderung tidak mengikuti pola yang ditetapkan oleh guru. Hal ini dikarenakan kegiatan pengenalan konsep pola diberikan dengan menggunakan buku kegiatan. Hal ini mengakibatkan anak merasa bosan dan bosan saat mengerjakan tugas dalam mengenali pola. Dalam pengenalan pola, Anda harus menggunakan kegiatan yang memudahkan anak mengenali pola. Kegiatan yang diberikan berupa kegiatan bermain, karena pada dasarnya dunia anak adalah dunia bermain. Teknik analisis data menggunakan uji-t. Dari hasil analisis pengujian hipotesis, ditunjukkan dari hasil analisis data bahwa thitung sebesar 31,25 lebih besar dari ttabel sebesar 1,72913 pada taraf tercapai 0,05 dan 2,53948 serta pada taraf yang dicapai sebesar 0,01. Hal ini menunjukkan bahwa nilai t tabel lebih kecil dari nilai t hitung baik pada tingkat signifikansi 0,05 maupun pada tingkat 0,05 dan pada tingkat 0,01. Dengan demikian Hipotesis Nol ditolak sehingga Hipotesis Kerja diterima. Dari tabel tersebut juga dapat dilihat bahwa nilai t hitung lebih besar dari nilai t tabel pada kedua tingkat yang dicapai, sehingga hasil yang didapat terbukti signifikan. Dengan demikian dapat disimpulkan bahwa media permainan meronce mempengaruhi kemampuan anak pada usia 4-5 tahun dalam mengenal bentuk geometris. Kata kunci : Media permainan meronce, Anak Usia Dini, Bentuk Geometri